Sediment Microstructure in Gas Hydrate Reservoirs and its Association With Gas Hydrate Accumulation: A Case Study From the Northern South China Sea - Bai, Chenyang; Su, Pibo; Su, Xin; Guo, Jujie; Cui, Hongpeng; Han, Shujun; Zhang, Guangxue (Frontiers in Earth Science, 2022)
Exploration and pilot production have confirmed that gas hydrates in the Shenhu area on the northern continental slope of the South China Sea have enormous resource potential. However, a meticulous depiction of gas hydrate reservoirs based on sediments is limited. The distributed low-flux gas hydrates are mainly deposited in the Shenhu area, and the gas hydrate saturation exhibits extreme vertical heterogeneity. In this study, we focused on the sediment microstructure of gas hydrate reservoirs. Based on the variation in gas hydrate saturation, the study interval was divided into non-gas hydrate (non-GH) as well as I-, II-, and III-gas hydrate reservoir layers. We analyzed the relationship between sediment microstructure and gas hydrate reservoirs based on computed tomography scans, specific surface area analysis, and scanning electron microscopy observations. The results showed that the sediment in gas hydrate reservoirs had three types of pores: 1) intergranular pores between coarse grains (CG-intergranular pores), 2) intergranular pores between fine grains (FG-intergranular pores), and 3) biologic grain pores (BG-pores). The CG- and FG-intergranular pores were mainly formed by the framework, which consisted of coarse minerals (such as quartz and feldspar) and clay minerals, respectively. The BG-pores were mainly formed by the coelomes of foraminifera. CG-intergranular pores and BG-pores can provide effective reservoir space and increase the permeability of sediment, which is conducive to gas hydrate accumulation. The FG-intergranular pores reduce permeability and are not conducive to gas hydrate accumulation. Clay minerals and calcareous ultramicrofossils with small grain sizes and complex microstructures fill the effective reservoir space and reduce the permeability of sediment; additionally, they improve the adsorption capacity of sediment to free gas or pore water, which is not conducive to gas hydrate formation and accumulation. The results of our study explicitly suggest that the microstructure of sediment is an important controlling factor for gas hydrate accumulation and reveals its underlying mechanism.